The Conservative Party and the Extreme Right 1945-1975. - Pitchford, Mark (Manchester University Press, 2011)
This book reveals the Conservative Party?s relationship with the extreme right between 1945 and 1975. For the first time, this book shows how the Conservative Party, realising that its well known pre-Second World War connections with the extreme right were now embarrassing, used its bureaucracy to implement a policy of investigating extreme right groups and taking action to minimise their chances of success. The book focuses on the Conservative Party?s investigation of right-wing groups, and shows how its perception of their nature determined the party bureaucracy?s response. The book draws a c.